A French Daily Backed by American Interests: Le Matin, 1884-1890 - Dominique Pinsolle (Transatlantica)
Le Matin (1884-1944) was the first French daily with an American style. This newspaper is well-known as one of the most important French papers published between the end of the nineteenth century and 1944. What is less well-known is that it was first backed by American interests. These American businessmen wanted to control a Parisian daily to make money and to promote their business projects. But they became very quickly unable to reach their goals in France and were forced to leave Le Matin and to sell it to its Parisian editor.